Relationship between adipokines and periodontitis - Reiko Furugen; Hideaki Hayashida; Masayasu Kitamura; Toshiyuki Saito (Elsevier, 2010)
Obesity is associated with an increased risk for developing characteristic features of metabolic syndrome, including hypertension, type 2 diabetes, and dyslipidemia. Interestingly, chronic exposure to periodontal pathogens' endotoxin and increased cytokine production have been proposed to enhance the risk for causing type 2 diabetes and cardiovascular complications. Obesity has also recently been reported to be associated with periodontitis. Obesity induces macrophage accumulation in adipose tissue, promotes chronic low-grade inflammation, and increases adipokines derived from adipocytes. In this review, we summarize recent advances in understanding the roles of adipokines in chronic inflammatory states such as periodontitis and focus primarily on adiponectin, leptin, and resistin. Understanding the role of adipokines may help elucidate relationships among periodontitis, obesity, type 2 diabetes, and cardiovascular diseases.